Violence Against Women During the Covid-19 Pandemic - Jumriani Nawawi (Musamus Law Review, 2022)
The COVID-19 pandemic that has hit the world has had a huge impact. Women are one of the groups affected by the pandemic. Legal protection for women has been established and has permanent legal force. However, the reality is that violence against women continues both culturally and structurally. This article describes the impact of the pandemic on women and efforts to eliminate violence against women during the pandemic. This research was conducted by systematically examining the laws and regulations and by using the technique of collecting document studies from the results of research on violence against women. The results of the study describe that COVID-19 has had a tremendous impact on women in terms of achieving sustainable development goals in Indonesia. During the COVID-19 pandemic, violence against women has increased.